Bagaimana Kecerdasan Emosional Dan Lingkungan Kerja Mempengaruhi Kinerja SMA Guru Di SMAN 1 Aluh-Aluh - Ridho Muarief (P3I Politeknik Negeri Madiun, 2020)
This research aims to know the emotional intelligence and working environment at SMAN 1 Aluh-Aluh, to know the performance of high school teachers of SMAN 1 Aluh-Aluh. to analyse how emotional intelligence and work environment impact the performance of high school teachers in SMAN 1 AluhAluh.The research methods used are descriptive analysis and verificative and operate the calculations using the SPSS 23.0 program. Variables in this research are emotional intelligence, work environment and teacher performance. Collection of data obtained through questionnaires, observations, interviews, and library studies. The sample withdrawal technique is non probability sampling. This research is the teacher of SMAN 1 Aluh-Aluh which amounted to 31 people. The results of this study concluded that: 1) Emotional intelligence at SMAN 1 Aluh-Aluh belongs to high category. 2) Working environment at SMAN 1 AluhAluh belongs to high category. 3) The performance of Guru in SMAN 1 Aluh-Aluh High School belongs to the category height. 4) Emotional intelligence partially affects significantly to teacher performance. 5) The working environment partially affects the teacher's performance. 6) The Emotional intelligence and working environment are simultaneously influential to the teacher's performance. It can be concluded that there is an influence between the emotional intelligence and the working environment to the teacher performance in SMAN 1 Aluh-Aluh Teacher.